Simultaneous nitrogen and carbon removal in a single biological aerated filter by the bioaugmentation with heterotrophic-aerobic nitrogen removal bacteria - Wang, HaiZhen; Gao, Qiang; Shufeng Liu; Qian Chen (Environmental TechnologyEnvironmental Technology, 2021)
Agrobacterium sp. LAD9 capable of heterotrophic-aerobic nitrogen removal was applied into a single biological aerated filter (BAF) for bioaugmented treatment of municipal wastewater. The achievement of simultaneous nitrogen and carbon removal in the bioaugmented system was systematically evaluated by ratios of COD to nitrogen (COD/N), ranging from 1 to 20. The results showed that at an appropriate COD/N ratio of 10, the BAF exhibited excellent carbon and nutrients removal, the averaged removal efficiencies for COD, NH4+-N and TN were 92.3%, 100% and 80.0%, respectively. Long-term operation of the bioaugmented system also confirmed the stability of the treatment efficiency. Further comparisons of SOUR and PCR-DGGE profiles between the bioaugmented and the control system revealed that the introduction of strain LAD9 greatly changed the structure of original microbial community and facilitated their capabilities of aerobic nutrients removal. The proposed bioaugmentation strategy is of particular importance to upgrading or retrofitting concurrent municipal wastewater treatment systems. [GRAPHICS] .